Spatially distributed freshwater demand for electricity in Africa - Gerbens-Leenes, P. W.; Vaca-Jiménez, S. D.; Holmatov, Bunyod; Vanham, Davy (Royal Society of Chemistry, 2024)
Although energy requires large amounts of water for its production, (inter)national statistics or reports on water demand for electricity for the African continent are scarce. Here we provide the spatially most detailed analysis presently available on freshwater demand for electricity for the recent year 2020, covering the whole of Africa. We conduct a major data mining effort using only freely accessible data. This results in 2534 individual power plants, including 1447 fossil (coal, oil and natural gas), 1071 renewable (wind, sun, biomass, geothermal and hydropower with the distinction between reservoir and run-of-river or ROR hydropower) and 16 other (waste heat and nuclear) power plants. We categorized the power plants according to applied fuel, operation cycle, infrastructure, cooling system and local climate. The total water withdrawal (WW) and consumption (WC) amount to 33 108 and 23 822 million m3 per year (Mm3 per year) respectively, for an annual electricity production of 1 050 674 GWh. Hydropower and natural gas, which have high water withdrawal intensities relative to other energy sources such as wind or sun, account for the largest fractions (70% and 27%, respectively) of total water withdrawal. Our database can be used at any spatial level, as we show results on the national, subnational and river basin level. Countries with high annual WW amounts include Egypt (8937 Mm3 ), Ghana (7893 Mm3 ), Zambia (5262 Mm3 ), Mozambique (2602 Mm3 ), Nigeria (2309 Mm3 ) and South Africa (1068 Mm3 ). River basins with high WW amounts include the Nile (10 377 Mm3 ), the Volta (7765 Mm3 ), the Zambezi (7596 Mm3 ) and the Niger (2562 Mm3 ) river basins. In major river basins, these WW amounts do not exceed 10% of renewable water availability, except for the Volta basin, where the value is 43%. By providing all results in a fully open-access database, we provide valuable statistics for any water management or energy stakeholder working in or on Africa.